2018
DOI: 10.1055/s-0037-1617456
|View full text |Cite|
|
Sign up to set email alerts
|

Preterm Preeclampsia with Severe Features: Composite Maternal and Neonatal Morbidities Associated with Fetal Growth Restriction

Abstract: Women with preterm PE with severe features and FGR, when compared with those with AGA, have significantly higher risk of CMM and CNM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It is associated with the development of hypertension and proteinuria after 20 weeks of pregnancy in previously normotensive and non-proteinuric women [ 4 , 5 ]. It complicates between 3% and 5% of pregnancies [ 1 , 6 , 7 , 8 ]. It is one of the leading causes of maternal and perinatal morbidities and mortalities around the world [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is associated with the development of hypertension and proteinuria after 20 weeks of pregnancy in previously normotensive and non-proteinuric women [ 4 , 5 ]. It complicates between 3% and 5% of pregnancies [ 1 , 6 , 7 , 8 ]. It is one of the leading causes of maternal and perinatal morbidities and mortalities around the world [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the leading causes of maternal and perinatal morbidities and mortalities around the world [ 1 , 2 ]. It is responsible for 76,000 maternal and 500,000 perinatal deaths annually [ 1 , 6 , 7 , 8 ] and 192 maternal deaths daily [ 7 ]. These figures demonstrate the enormity of the ills of pre-eclampsia and the need to find ways of preventing the complications associated with it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preeclampsia is a pregnancy-specific disorder resulting in hypertension and multiorgan dysfunction, 1 and is a leading cause of maternal and neonatal morbidity and mortality, affecting patients’ long-term quality of life. 2 Low-dose administration of aspirin before 16 weeks of gestation has been reported to effectively reduce preterm preeclampsia. 3 Therefore, novel biomarkers with high sensitivity and specificity are needed to contribute to early screening of high-risk patients, in order to effectively prevent or delay the occurrence and development of preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…Balogun et al [24] claimed that preterm preeclamptic parturients with fetal growth restriction have higher composite maternal and neonatal morbidity risk than appropriate for gestational age cases. Similarly, Haddad et al [25] showed that severe fetal growth restriction is associated with increased fetal death risk while maternal complications were not different in preterm severe preeclampsia cases.…”
Section: Discussionmentioning
confidence: 99%